A comparison of microstructure and uniaxial compressive response of ice-templated alumina scaffolds fabricated from two different particle sizes. Issue 14 (1st November 2016) - Ghosh, Dipankar; Dhavale, Nikhil; Banda, Mahesh; Kang, Hyungsuk
Abstract: This study investigates the effects of two different particle sizes (0.3 μ m vs. 0.9 μ m ) on the microstructure and uniaxial compressive response of ice-templated sintered alumina scaffolds as a function of the solids loading of the ceramic suspensions and freezing front velocity (FFV). For a comparable solids loading and FFV, variation of the particle size is observed to have a significant effect on the microstructure of the fabricated scaffolds. Moreover, transition of the pore morphology with the increasing solids loading and FFV is observed to be more drastic for the scaffolds processed from the 0.9 μ m size powder particles compared to the scaffolds processed from the 0.3 μ m size powder particles. Similarly, particle size variation also influenced significantly the relative density and porosity of the scaffolds. Interestingly, in spite of the observed significant differences of the microstructure and relative density, uniaxial compressive stress-strain measurements revealed marginal effects of the particle size variation on the compressive strength. The measured comparable uniaxial compressive response of the sintered alumina scaffolds fabricated from two different particle sizes are rationalized based on the relative density, pore aspect ratio, and interlamellae bridge density.